IMPLEMENTASI MAUT PADA SISTEM PENDUKUNG KEPUTUSAN DALAM DISTRIBUSI PERSEDIAAN KANTONG DARAH DI UDD PMI KOTA LHOKSEUMAWE: IMPLEMENTATION OF MAUT IN DECISION SUPPORT SYSTEMS FOR BLOOD BAG DISTRIBUTION AT THE PMI BLOOD TRANSFUSION UNIT IN LHOKSEUMAWE CITY - Roza Tarina; Safwandi Safwandi; Yessy Afrillia (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
The Blood Donor Unit (UDD) of PMI Lhokseumawe City has a vital role in maintaining the availability and distribution of blood bags to various hospitals. However, the distribution process is faced with the challenge of a mismatch between the number of requests and fluctuating supplies, which risks disrupting medical services and causing waste due to expired blood. This study aims to design and implement a web-based decision support system (SPK) that assists PMI UDD in prioritizing the distribution of blood bags objectively and efficiently. The method used is Multi-Attribute Utility Theory (MAUT), with evaluation of six main criteria: number of uses, number of supplies, number of requests, road density, travel time, and distance. The system was built using PHP and MySQL, and tested using the black-box testing method. The test results show that all system features work validly according to the expected functionality, thus supporting the reliability of the application in the decision-making process. The MAUT calculation results show that RSU Metro Medical Center obtained the highest utility value of 0.5809 (58.09%), placing it as the top priority for distribution. In comparison, RSU Cut Meutia obtained 0.4234 (42.34%), while RSIA Bunda obtained 0.3997 (39.97%), which shows a significant difference in distribution priorities. The implementation of this system is expected to improve distribution effectiveness, optimize inventory allocation, and support more accurate and measurable decision-making at UDD PMI Lhokseumawe City.